Cost-Effectiveness of Percutaneous Lymphatic Embolization for Management of Plastic Bronchitis. Issue 4 (July 2019) - Benjamin, Jamaal L.; Rychik, Jack; Johnstone, Jordan A.; Nadolski, Gregory J.; Itkin, Maxim
Background: Plastic bronchitis is a dreaded complication of single ventricle physiology occurring following palliation via Fontan procedure. Medical management of plastic bronchitis often fails, requiring heart transplantation. Percutaneous lymphatic embolization is an emerging treatment for plastic bronchitis. Methods: To determine the cost-effectiveness of competing management strategies, a modified Markov model was constructed with patients transiting through treatments—medical management, lymphatic embolization, or heart transplantation from a hospital system perspective. Health state transitions were modeled using an institutional review board–approved retrospective review of the Children's Hospital of Pennsylvania's plastic bronchitis cohort. Medication pricing data were obtained from the National Inpatient Sample. Differences in costs and quality-adjusted life years (QALYs) over a five-year horizon for each group were determined. The incremental cost-effectiveness ratio was then calculated. Results: The mean cost of lymphatic embolization from procedure performance was US$340, 941, US$385, 841 for heart transplantation, and US$594, 520 for medical management. The mean quality-adjusted survival of lymphatic embolization yielded an additional 0.66 QALYs ( P < .03) relative to heart transplantation and 1.3 ( P < .0001) relative to medical management. Orthotopic heart transplantation yielded an additional 0.66 QALYs ( P = .06) when comparing heart transplantation to medical management. Compared to medical management, lymphatic embolization generated an incremental cost-effectiveness ratio of US$192, 105. Similarly, compared to heart transplantation, lymphatic embolization yielded an incremental cost-effectiveness ratio of US$68, 030. Conclusions: Of the available plastic bronchitis treatments, with a willingness to pay of US$150, 000, lymphatic embolization produces an incremental cost-effectiveness ratio within the bounds considered to be cost-effective, potentially causing financial benefits to the health system.